If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + 2(5c + -2) = 29answer Reorder the terms: 13 + 2(-2 + 5c) = 29answer 13 + (-2 * 2 + 5c * 2) = 29answer 13 + (-4 + 10c) = 29answer Combine like terms: 13 + -4 = 9 9 + 10c = 29answer Solving 9 + 10c = 29aenrsw Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 10c = -9 + 29aenrsw Combine like terms: 9 + -9 = 0 0 + 10c = -9 + 29aenrsw 10c = -9 + 29aenrsw Divide each side by '10'. c = -0.9 + 2.9aenrsw Simplifying c = -0.9 + 2.9aenrsw
| 6(7-3x)=60 | | 9x+y=4 | | 3(1-2x)=4-6x | | 6n-13=5n+11 | | 5(4x+3)=-25 | | 2(-7+3x)=46 | | 2-(m+4)=3m-2 | | 5x-3+667=51x | | 3(5-4x)=75 | | 2(2w+5)+2w=46 | | 11a+9-3a=-7 | | 0.6(100-x)+0.4x=0.5(92) | | -x-3(7)=10 | | -x-3y=10 | | (9-2y)+2y=13 | | -6x-y=-1 | | -5(2V-X+4)= | | 9x+2x= | | R+9+7r=4(3+2r)-3 | | 2a+3(2+a)= | | x-2+4x=13 | | abs(4x-9)=4 | | 3z+2=z-3 | | 149-6x=39x+19 | | 4a-3b-7a-3b= | | 34-19k=34 | | 6x-x+3= | | 7-7x=197-42x | | 4a+3a= | | -82-10x=10x+18 | | 4x+14=-41-7x | | 12-2x=2+3x |